Booster vaccination with hexavalent DTPa-HBV-IPV/Hib vaccine in the second year of life is as safe as concomitant DTPa-IPV/Hib + HBV administered separately - Saenger, R.; Maechler, G.; Potreck, M.; Zepp, F.; Knuf, M.; Habermehl, P.; Schuerman, L. (Vaccine, 2005)
The safety and reactogenicity of a booster dose of GSK Biologicals’ hexavalent DTPa-HBV-IPV/Hib vaccine ( N = 4725) was compared with the separate administration of GSK Biologicals’ DTPa-IPV/Hib and HBV vaccines ( N = 4474) in two open, randomized multicenter studies (A and B). Solicited symptoms occurring within 4 days of vaccination were recorded on diary cards and serious adverse events (SAEs) were collected throughout the study period. In Study A ( N = 1149), incidences of solicited symptoms were similar in both groups; there were no SAEs either reported within 4 days of vaccination or considered to be causally related to vaccination. In study B ( N = 8050), where fever was the only solicited symptom, rectal temperature ≥39.5 °C was observed in 2.5% and 2.8% of the subjects, respectively. Fever ≥40.0 °C was rare (0.6%), and only two cases of febrile convulsions were recorded during the 4 days following vaccination both in the control group. Large swelling reactions (defined as local injection site swelling with diameter >50 mm, noticeable diffuse injection site swelling or noticeable increased circumference of the injected limb) were reported following 2.3% of the booster vaccine doses, regardless of the vaccine used. Extensive swelling reactions involving an adjacent joint were reported in 0.1% of the subjects. Two SAEs, both reported after booster doses of DTPa-IPV/Hib and HBV vaccines administered separately, were considered by the investigators to be related to vaccination. Both resolved completely without sequelae. The hexavalent DTPa-HBV-IPV/Hib vaccine and the DTPa-IPV/Hib and HBV vaccines administered separately have similar good reactogenicity and safety profiles when given as booster doses in the second year of life.